2013
DOI: 10.1016/j.schres.2013.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Symptom dimensions and functional impairment in early psychosis: More to the story than just negative symptoms

Abstract: Functional impairment is a defining feature of psychotic disorders and usually appears well before their onset. Negative symptoms play a prominent role in the impaired functioning of individuals with schizophrenia and those at clinical-high-risk (CHR) for psychosis. Despite high rates of depression and anxiety in early psychosis, few studies have examined the contribution of these symptoms to functioning in the putative ‘prodrome.’ In the current study, we tested the hypotheses that 1) worse negative and disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 60 publications
4
65
1
1
Order By: Relevance
“…Of note, recent studies of high risk, prodromal and early psychosis populations have identi fied negative symptoms as the strongest predictors of social function. 38,39 Our sample, however, consisted of individuals with chronic illness, further emphasizing the importance of phasespecific investigation of symptoms and their impact.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, recent studies of high risk, prodromal and early psychosis populations have identi fied negative symptoms as the strongest predictors of social function. 38,39 Our sample, however, consisted of individuals with chronic illness, further emphasizing the importance of phasespecific investigation of symptoms and their impact.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional evidence indicated that negative symptoms (Niendam et al, 2006b;Cornblatt et al, 2007;Svirskis et al, 2007;Willhite et al, 2008;Velthorst et al, 2010;Raballo et al, 2011;Valmaggia et al, 2013;Walder et al, 2013;Meyer et al, in press) and disorganised and general symptoms (Cornblatt et al, 2007;Comparelli et al, 2010;Velthorst et al, 2010;Corcoran et al, 2011;Fulford et al, 2013;Kim et al, 2013;Walder et al, 2013;Meyer et al, in press) were consistently associated with a broad range of global, social and role functioning measures. When each of these symptom clusters was entered into regression analyses, only negative symptoms remained significantly associated with poor functioning Fulford et al, 2013;Kim et al, 2013;Meyer et al, in press).…”
Section: Symptomsmentioning
confidence: 99%
“…In addition to the development of psychosis (Yung et al, 2003;Mason et al, 2004;Thompson et al, 2011;Cornblatt et al, 2012), there has recently been a growing interest in poor functioning as an outcome of interest in itself (Yung et al, 2010;Barbato et al, 2013;Fulford et al, 2013;Kim et al, 2013;Lin et al, 2013) and in identifying factors predictive of long-term functional disability (Fusar-Poli et al, 2009;Lin et al, 2011;Carrión et al, 2013;Meyer et al, in press). For a large proportion of ARMS patients functioning remains impaired, regardless of transition to full-threshold psychosis or symptomatic remission (Addington et al, 2011a;Schlosser et al, 2012;Carrión et al, 2013;de Wit et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, given that cognitive control mechanisms are involved not just in inhibitory but also in facilitatory processes (e.g., generation and maintenance of goal representations [67]), impaired engagement of cognitive control mechanisms to downregulate negative affective information could be accompanied by a complementary deficit in the upregulation of positive affective information. Failure to upregulate positive emotion may underlie anticipatory pleasure deficits observed in psychosis [126][127][128] and CHR individuals [129], and could contribute to associated reward/motivational impairments thought to contribute to negative symptoms of anhedonia and avolition [130,131]. Conversely, failure to downregulate positive emotion may underlie approach-motivation and rewardprocessing abnormalities observed in affective psychoses such as bipolar disorder [132,133].…”
Section: Discussionmentioning
confidence: 99%